Strategi Pemasaran Digital: Meningkatkan Minat Calon Jemaah pada Biro Perjalanan Haji dan Umrah Melalui Media Sosial - Istiqomah, Nur Hidayatul; Ghofir, Jamal; Husniyah, Latifatul (ASWALALITA: Journal of Da'wah Management, 2024)
This research aims to delve into the impact of digital marketing strategies through social media in increasing the interest of prospective pilgrims towards Hajj and Umrah travel agencies. The primary focus of this study is to analyze the effectiveness of utilizing social media platforms, such as Instagram and Facebook, in shaping brand awareness, stimulating the interest of prospective pilgrims, and building positive interactions. The research methodology employed is library research to explore literature and research findings related to digital marketing strategies in the Hajj and Umrah travel industry. The research findings indicate that creative visualization through social media plays a pivotal role in shaping positive perceptions and enhancing the interest of prospective pilgrims. Active engagement, quick responses to inquiries, and feedback management have also proven to strengthen the relationship between travel agencies and prospective pilgrims. However, challenges such as online reputation management and intensifying competition necessitate active monitoring, proactive responses, and differentiation strategies. The conclusion of this research provides profound insights into the role of digital marketing strategies through social media in enhancing the interest of prospective pilgrims in Hajj and Umrah travel services.